Kompoen Sikap Mahasiswi yang Aktif pada Organisasi Eksternal Kampus - Rahmayana, Feby; Siregar, Nani Restati; Marhan, Citra (Jurnal Sublimapsi, 2024)
Students who are active in external campus organizations are supported by the quality and services available in the organization. The desire of female students to be active in external campus organizations is influenced by the attitude component. The attitude component is a variable that is thought to be able to influence the attitude of female students to be active in external campus organizations. Therefore, this study was conducted with the aim of knowing the percentage value of the attitude component of female students who are active in external campus organizations and describing the percentage results. The sampling technique used cluster random sampling, so that a sample size of 57 female students was obtained from a population of 570 female students who were active in campus external organizations in Kendari city, Southeast Sulawesi Province. Data collection methods using cognitive, affective, and conative scales. Data analysis techniques in this study using descriptive analysis. Descriptive analysis explains the mean, standard deviation, and categorization of respondents. Categorization is intended to place respondents into groups whose positions are tiered according to a continuum based on the measured attributes. The results showed that the cognitive component obtained a value of 63%, which can then be categorized as moderate. The affective component obtained a value of 54%, this can be categorized as moderate. The conative component obtained a value of 49% which can then be categorized as moderate.Keywords: Attitude Component;Campus External Organizatio; StudentAbstrak: Mahasiswi yang aktif pada organisasi eksternal kampus karena didukung oleh kualitas dan pelayanan yang ada pada organisasi tersebut. Keinginan mahasiswi untuk aktif dalam organisasi eksternal kampus dipengaruhi oleh komponen sikap. Komponen sikap merupakan variabel yang diduga mampu mempengaruhi sikap mahasiswi untuk aktif pada organisasi eksternal kampus. Oleh karena itu, penelitian ini dilakukan dengan tujuan untuk mengetahui nilai peresentase komponen sikap mahasiswi yang aktif pada organisasi eksternal kampus dan mendeskripsikan hasil persentase tersebut. Teknik pengambilan sampel menggunakan cluster random sampling, sehingga diperoleh jumlah sampel sebesar 57 mahasiswi dari 570 populasi mahasiswi yang aktif pada organisasi eksternal kampus di kota Kendari Provinsi Sulawesi Tenggara. Metode pengumpulan data menggunakan skala kognitif, afektif, dan konatif. Teknik analisis data dalam penelitian ini menggunakan analisis deskriptif. Analisis deskriptif menjelaskan rerata (mean), standar deviasi, dan kategorisasi responden. Pengkategorisasian dimaksudkan untuk menempatkan responden ke dalam kelompok-kelompok yang posisinya berjenjang menurut suatu kontinum berdasar atribut yang diukur. Hasil penelitian menunjukkan bahwa komponen kognitif memperoleh nilai 63% selanjutnya dapat dikategorikan sedang. Komponen afektif memperoleh nilai 54% hal ini dapat dikategorikan sedang. Komponen konatif memperoleh nilai 49% selanjutnya dapat dikategorikan sedang.Kata Kunci: komponen sikap; mahasiswi; organisasi eksternal kampus